2015
DOI: 10.1016/j.acra.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Prone Versus Supine Breast FDG-PET/CT for Assessing Locoregional Disease Distribution in Locally Advanced Breast Cancer

Abstract: Rationale and Objectives Prone F-18 fluorodeoxyglucose (FDG)-PET/CT may have advantages for breast imaging due to improved separation of deep anatomical structures. There are limited data on whether prone and supine FDG-PET/CT provide similar information regarding breast and axillary disease in the setting of locally advanced breast cancer (LABC). The purpose of this study was to compare the information on locoregional disease distribution provided by prone versus supine FDG-PET in newly diagnosed LABC. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…6 To our knowledge, the current study is the first to characterize the prone positioner and systematically measure-with assessment of and correction for withinpatient uptake time variability-differences, both in terms of two clinically relevant semiquantitative endpoints, SUV peak and SUV max , in 18F-FDG-PET/CT images acquired in the prone versus conventional supine orientations. Prone PET imaging, with the customized torso support device, is now validated for SUV measurements compared to prone imaging without the device.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…6 To our knowledge, the current study is the first to characterize the prone positioner and systematically measure-with assessment of and correction for withinpatient uptake time variability-differences, both in terms of two clinically relevant semiquantitative endpoints, SUV peak and SUV max , in 18F-FDG-PET/CT images acquired in the prone versus conventional supine orientations. Prone PET imaging, with the customized torso support device, is now validated for SUV measurements compared to prone imaging without the device.…”
Section: Resultsmentioning
confidence: 94%
“…4,5,7,8 We have recently completed a preliminary analysis comparing prone and supine PET in the qualitative categorization of the anatomical distribution of disease and in the assessment of the number of involved axillary lymph nodes in LABC patients. 6 As an extension of that effort, the current study was undertaken to quantitatively compare clinically relevant metrics (SUV peak , SUV max ) derived from prone versus supine PET. To accomplish this, we first set out to systematically examine the 18F-FDG-PET properties of a dedicated, custombuilt prone positioning device in conjunction with phantoms simulating conditions found in prone and supine patient PET/CT scans (Figs.…”
Section: A Motivations For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Images were collected using a Discovery STE clinical PET/CT scanner (GE Healthcare, Waukesha, WI, USA). Data were acquired in the prone position using a custom-built padded support [25][26][27][28] . A low-mAs CT scan was acquired using the smart mA setting for attenuation correction of the emission data.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
“…FDG PET/CT mammography reportedly images a wider area of the axillary fossa so that the anatomic structures of the axilla can be more easily differentiated from one another than is possible using whole-body PET/CT, even though there were no significant differences in the number of metastatic axillary lymph nodes that could be detected between these two types of study [5,35,48]. Koolen et al [49] reported that combining prone and standard supine FDG PET/CT detected locoregional lymph node metastases with a sensitivity of 82 % and a specificity of 92 %, which changed the indication for radiotherapy in a substantial proportion of patients based on detection of occult N3 nodes.…”
Section: Regional Lymph Node Assessmentmentioning
confidence: 99%